Pengaruh Stres Kerja dan Beban Kerja terhadap Kinerja SKPD Kabupaten Sintang Kalimantan Barat - Niken Widyastuti (Universitas Proklamasi 45 Yogyakarta, 2015)
The purpose of this study is to determine the effect of stress at work and workload the performance as partial and simultaneous toward to SKPD performance in Kabupaten Sintang Kalimantan Barat. This study had used Descriptive Quantitative methode as main methode and Exhaustive Sampling as sampling methode. Sample were taken as a whole from thepopulation, that is 75 employees. Data were taken by using list of question, interviews, and literature searching. Data were analyzed by using Regression Methode and through SPSS program for Windows. The result of the study have shown that stress at work and workload significantly influence the employee’s performance, with value of determintation was 0,681 or 68,1%. Stress at work and workload had significantly influencing employee’s to SKPD performance in Sintang Kalimantan Barat. For the next study, all considered, would be better if the next researcher added another variables that maybe had some contribution in employee’s performance, such as working satisfication, neighbourhood, culture in work, reward, compensation and personality.